2020
DOI: 10.1002/jgc4.1238
|View full text |Cite
|
Sign up to set email alerts
|

A Systematized review of experiences of individuals in Arnett’s emerging adulthood stage who live with or are at‐risk for genetic conditions

Abstract: Emerging adulthood, a distinct developmental period between ages 18 and 29 years, comprises five features: identity exploration, experimentation/possibilities, negativity/instability regarding one's outlook, self-focus, and feeling in-between adolescence and adulthood. A growing literature examines the impact of genetic conditions on individuals who chronologically fit the emerging adulthood period. This systematized literature review uses the emerging adulthood theory to determine whether individuals living w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(347 reference statements)
0
5
0
Order By: Relevance
“…The age of instability brings numerous life transitions, as emerging adults are transitioning to college or the workplace, moving out of home and expanding social and support networks (Wiebe et al, 2016). Previous research has found that during this period emerging adults have many competing priorities (Audulv et al, 2009) and those living with LTPC need to consider and be cautious of their social environment and balance it with their treatment regime (Shelley et al, 2020). The findings of this review highlight that emerging adults living with LTPC also have many life transitions and that these transitions and new schedules (e.g., college, work, moving out of home), can have a negative effect on the ability to carry out self-management tasks (e.g., taking medication, eating habits, rest and exercise) (Ersig, 2019;Johnson & Annesi, 2018;Saylor et al, 2019Saylor et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The age of instability brings numerous life transitions, as emerging adults are transitioning to college or the workplace, moving out of home and expanding social and support networks (Wiebe et al, 2016). Previous research has found that during this period emerging adults have many competing priorities (Audulv et al, 2009) and those living with LTPC need to consider and be cautious of their social environment and balance it with their treatment regime (Shelley et al, 2020). The findings of this review highlight that emerging adults living with LTPC also have many life transitions and that these transitions and new schedules (e.g., college, work, moving out of home), can have a negative effect on the ability to carry out self-management tasks (e.g., taking medication, eating habits, rest and exercise) (Ersig, 2019;Johnson & Annesi, 2018;Saylor et al, 2019Saylor et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging adulthood is a period during which emerging adults are exploring and expanding their networks beyond the family (Hopmeyer et al, 2022; Wiebe et al, 2016). Previous research has highlighted that in addition to being important for the transition to adulthood, navigating shifting interpersonal influences and changes to support systems (e.g., familial support) is also important for the self-management of LTPC during emerging adulthood (Rasalingam et al, 2021; Shelley et al, 2020; Wentzell et al, 2020). This review provides support for this in highlighting the changes in support systems (e.g., college peers) and how relationships, especially family, can act either as a facilitator or as a barrier to self-management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that, college students are in the exploration stage of their career (Super, 1980), and the uncertainty of identity exploration can easily lead to confusion and pressure (Shelley et al, 2020). Data from the 2022 White Paper on Learning and Development of Chinese College Students show that "confusion about the future" accounts for the largest proportion of the growing pain points of college students.…”
Section: Introductionmentioning
confidence: 99%